IMPLEMENTATION OF GREEN SUPPLY CHAIN MANAGEMENT FOR PRODUCTION: A CASE STUDY IN SONY (MALAYSIA) SDN. BHD. - Choong, Chien Khay; Chew, Boon Cheong; Hamid, Syaiful Rizal (Journal of Technology Management and Business, 2015)
Nowadays each company is going green due to global greenhouse gases emission has reached a critical level and awaked the social awareness. Companies are requested to be responsible for all direct or indirect pollution of their act. Malaysia Green Technology Corporation (Green Tech Malaysia) has embarked on a carbon footprint (CFP) labeling project to help the customer differentiate between green and non-green product, with the support of policy it will affect the customer purchase decision. Therefore organizations need a way to comprehensively manage their entire business in a manner that meets green and profitability targets in order to maintain their competitive advantages. Green supply chain management (GSCM) is designed to consider the environmental effects of all processes of supply chain from the extraction of raw material to the final disposal of goods to achieve minimized environmental impact while assuring maximized consumer satisfaction. Thurs GSCM Green supply chain management (GSCM) will be a key approach for an organization to make sure their businesses are environmentally sustainable. In this case study SONY Malaysia Sdn. Bhd. was selected to investigate the process to implement GSCM and the activities that involved at each process to allow the company imply the insertion of environment criteria within the decision –making context of the traditional supply chain management. The respondent of the study will be aims for 25 managers through interviews to ensure the research validity. This study proved that the application of GSCM in SONY brings a lot of benefits such as more social responsibility, inventory improvement and lowered the cost. As a conclusion, GSCM might become the most efficiency strategic for SONY to go green and it could be implementation for other manufactures that to transform their supply chain management.